Evaluation Of The Implementation Of Government Internal Control Systems On Collection Of Rural And Urban Land And Building Taxes In Southeast Minahasa District - TUMIMOMOR, Cherril Angelia; SAERANG, David Paul Elia; KAPOJOS, Peter Marshall (PT Keberlanjutan Strategis Indonesia, 2022)
The Rural and Urban Land and Building Tax is a tax on land and/or buildings that are owned, controlled, and/or utilized by individuals or entities, except for areas used for plantation, forestry and mining business activities. The government internal control system is an integral process for actions and activities carried out continuously by the leadership and all employees to provide adequate confidence in the achievement of organizational goals through effective and efficient activities, reliability of financial reporting, safeguarding state assets, and compliance with laws and regulations. The purpose of this study is to find out how the internal control system is applied to the collection of Rural and Urban Land and Building Taxes in Southeast Minahasa Regency. The research method used is descriptive qualitative. The results of the study show that the work or activities carried out are in accordance with the elements of the existing internal control system, except for the elements of control activities in the segregation of functions sub-elements which have not been carried out properly. The conclusion of this study is that for the elements of the control environment, risk assessment, information and communication and monitoring, control has been carried out in accordance with Government Regulation Number 60 of 2008 and has been implemented properly, while the elements of control activities have not been in accordance with Government Regulation Number 60 of 2008 and have not been implemented optimally.